Integrating social media marketing with esg-oriented brand strategies: Insights from retail engagement with gen z and millennials - Safira, Fitri Yani Rossa; Halim, Rizal Edy (Institute for Advanced Social, Science, and Sustainable Future, 2025)
Background: The use of social media has seen a significant increase worldwide, particularly in Indonesia. Social media has become a bridge for users to carry out various activities in the digital world, with companies, governments, and other organizations utilizing it to market their businesses. This phenomenon has led to the emergence of Social Media Marketing Activities influencing Brand Equity. Many companies, especially retail businesses in Indonesia, use Social Media Marketing to target Generation Z and Millennials. The aim of this study is to analyze the effect of Social Media Marketing on Brand Equity, mediated by Brand Love, among retail companies in Indonesia targeting Generation Z and Millennials. Methods: This research utilized a sample of 300 respondents who follow one of the retail companies on social media in Indonesia. Data collection was done through surveys, and the data were analyzed using statistical methods. Findings: The results show that Social Media Marketing Activities did not have a significant positive effect on Brand Equity. These findings suggest that certain aspects of Social Media Marketing need to be optimized for better effectiveness in reaching Generation Z and Millennials. Conclusion: The study concludes that understanding how to effectively leverage Social Media Marketing is crucial for retail companies targeting Generation Z and Millennials in Indonesia. Novelty/Originality of this article: This article offers new insights into the impact of Social Media Marketing on Brand Equity in the retail sector, with a focus on the Generation Z and Millennial demographics in Indonesia.